مساهمة الفاعل المحلي في استدامة الموارد المائية والترابية بالمجالات شبه الجافة المغربية حالة عبدة الشمالية بإقليم آسفي - تاموسيت, عثمان; لهلال, المامون (جامعة الوادي - University of Eloued, 2020)
تعتبر الموارد المائية والترابية من الأسس التي تقوم عليها كل تنمية فلاحية تستهدف الأرياف خاصة تلك الواقعة بالمجالات شبه الجافة التي تعاني، عموما، من عدم كفاية التساقطات وتذبذبها وضعف الموارد المائية وكذا ندرة التربات الخصبة. ويهدف هذا المقال إلى تسليط الضوء على تدخلات بعض الفاعلين المحلين الرسميين في تدبير تلك الموارد من أجل تطوير قدراتهم الفلاحين ومعارفهم وتحسين أوضاعهم الاجتماعية، وعلى الخصوص دور مؤسسات التعليم والإرشاد الفلاحيين. غير أن هذه المؤسسات تواجه إكراهات تحول دون قيامها بالدور المنوط بها زيادة على ضعف انفتاحها على مجال الدراسة، وهو ما سيجعل الفلاح المحلي يواجه الظروف الطبيعية الصعبة باللجوء إلى طرق متنوعة موروثة من الماضي أو مشجعة من طرف الدولة في إطار الدعم الممنوح لبعض الزراعات كتعبئة مياه التساقطات وتنويع التقنيات الفلاحية وتثمين المنتجات المجالية. Water and soil resources are regarded one of the foundations for every agricultural development, especially if they target the rural areas in semi-arid regions which generally suffer from inadequacy and fluctuation in rainfall, scarce water resources and the lack of fertile soils. This article aims to cast some light on the intervention of some official local actors in the management of these resources in order for farmers to develop their abilities and knowledge and improve their social status, particularly the role of educational institutions in providing farmers with agricultural advice and guidance. However, these institutions still face several challenges hampering them from fulfilling the role assigned to them. In addition to this, these institutions have not yet shown great openness to the geographical field of study in question, which will make the local farmer deal with harsh natural conditions by resorting to various methods, either inherited from the past or encouraged by the state, within the framework of subsidizing farming. Such methods include rainwater harvesting, diversification of agricultural technologies, and the valuing of local products.
The contribution of the local actor to the sustainability of water and soil resources in the Moroccan semiarid areas: the northern part of Abda, Safi region as a case study.
مقال
Keywords: الموارد المائية والترابية ; الارشاد الفلاحي ; التعليم الفلاحي ; الفلاح المحلي ; المنتجات المجالية